Abordagens Sobre Educação Inclusiva - Silveira, Jader Luís da (2020)
The e-book brings small considerations about Inclusive Education, the difficulties of implementation in practice and challenges faced by teachers and students. The issue of the multifunctional resource room and the instruments for the teaching-learning process to be successful are also discussed.